Algorithmic Mediation and Digital Platforms: Constructing Collective Consciousness in Wartime Ukraine - Yanishevskyi, Oleksandr (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The research examined how Internet media shape the collective consciousness of Ukrainians during ongoing social change and armed conflict. It identifies the major trends, thematic priorities, and influence mechanisms used by leading Ukrainian online outlets to mold public opinion. Methodology: The study used a multi-method design that blended quantitative and qualitative tools. Content analysis clarified the thematic focus and narrative patterns across selected media outlets. Mediametric and platform-aware analysis helped quantify how distribution algorithms, platform mechanisms, and engagement tools amplify certain narratives. This made it possible to track how digital platform architecture shapes narrative visibility and public resonance. A nationwide sociological survey of 1,600 respondents captured broader public perceptions. Main Findings: The findings reveal a significant differentiation in editorial strategies among Ukrainian online media. Content analysis indicates that UNIAN demonstrates the strongest emphasis on heroic narratives (55% of materials), whereas RBC-Ukraine shows a notably lower focus (35%). These editorial strategies and their divergent public impact are critically enabled and modulated by the underlying digital infrastructure, including algorithmic content prioritization and platform-afforded engagement loops, highlighting the need to analyze media influence through a techno-social lens. Novelty/Originality of this study: Online media play a decisive role in shaping public opinion in Ukraine, largely through how they frame self-identification, language policy, and views on the ongoing conflict. The study adds a media-technological lens to understanding collective consciousness, highlighting the impact of algorithmic curation, platform design, and data-driven narratives on opinion formation in wartime conditions.